Foreign direct investment in food manufacturing and stages of human development - Justice Gameli Djokoto; Paragon Pomeyie; Camillus Abawiera Wongnaa (Cogent Economics & Finance, 2023)
The extension of the shelf life of food through processing makes food available beyond the shelf-life of fresh agricultural produce, which has implications for food and nutrition security. Food processing creates products for the specified nutritional needs of persons with special nutritional requirements, market access for products from the agricultural sector, employment for households, opportunities for trade and marketing as well as tax revenues for the state. These contribute to the standard of living (income) as well as education and health components of human development. Existing studies have focused on assessing the human development (HD) effects of foreign direct investment (FDI). However, the differences in human development could engender differences in the effect of FDI on human development. Unlike the exante literature, we focus on food manufacturing FDI, the human development stages and the contemporaneous analysis of developed and developing countries. We used panel data from 18 and 26 developing and developed countries respectively from 1991 - 2021 and fitted it to panel generalised estimation equations and the general method of moments estimators. We find that food manufacturing FDI had a significant influence on human development for all human development stages in developing but only for low-developed countries in the category of the low human development index. Not isolating the influence of FDI on human development stages could produce misleading outcomes for developed countries. Policymakers can look at food manufacturing FDI to increase HDI and in some cases to migrate from one stage to another.
Keywords: L66; O11; Q18; F21; 63; 330; developed countries; developing countries; food production; general estimation equations